'A Very Fair Statement of His Past Life': Transported Convicts, Former Lives and Previous Offences. Issue 1 (5th October 2015) - Rogers, Helen
As mass digitization brings new opportunities for analysing criminal and convict records, this article considers how we can recover the personal histories of the convicted. It proposes 'intimate reading' as a complementary approach to large-scale data mining and distant reading methods currently used to examine large prison cohorts. Immersive reading, integrating quantitative and qualitative analysis of multiple sources, permits investigation of specific individuals, their interaction with others, and their engagement – however unequal – with the record-makers. It helps us detect the agency of those who left few traces of personal testimony but whose lives were captured in abstract information garnered by officialdom. The article focuses on male convicts who served time at Great Yarmouth in the 1830s and 1840s and were transported to Van Diemen's Land where arrivals were interrogated on their offending histories, occupations and family ties, while their bodies were inspected for distinguishing characteristics. Comparing convict records with other documentation on their former lives allows us to explore what exiles revealed and concealed from the authorities about their past. Record linkage on this cohort brings to light the under-reporting of prior convictions in convict records by around two-thirds and suggests that historians continue to underestimate the extent of previous offending among the transported population. Social profiling of this group exposes patterns in employment, family and social networks that are not so readily apparent when reading fragmentary evidence of individual lives. Small-scale data analysis enables us to decode the more personal testimony unwittingly preserved by the penal authorities when they described convicts' tattoos. The article concludes with an intimate reading of the elaborate tattoos of one Yarmouth convict that spectacularly depicted the man he felt himself to be.